SOURCING FUNGSI MSDM: SEBUAH ANALISIS TERHADAP KONTROVERSI KEPUTUSAN “MAKE OR BUY “ (Fokus Ekonomi, 2009)
Generally this paper explores the outsourcing decision towards human resource management (HRM) functions. The controversy regarding ‘make or buy’ decision between insourcing and outsourcing has generated many debates. Based on the literature review, the author has developed some conceptual frameworks to analyze under which situations and conditions and also what kinds of HRM functions can be better outsourced by the client to improve their competitiveness. The results suggest that the organization will be able to choose ‘make or buy’ decision based on some points of view such as the nature of HRM functions (strategic and critical), level of cost saving that can be achieved by the client, the relationship between the client and the vendor and the default risk of outsourcing, and also the client’s bargaining  power  towards  the  vendor. It is hoped that the conceptual  frameworks discussed in this paper will in the future guide in  empirical  research on outsourcing of HRM  functions and also provide a comprehensive analysis to HRM professionals in formulating  outsourcing  decision.